A Single-Center Analysis of Sex Differences in Patients With Chronic Subdural Hematoma in China - Ou, Yunwei; Fan, Wenhua; Yu, Xiaofan; Wu, Liang; Liu, Weiming (Frontiers in Neurology, 2022)
Background Given the men's predominance in the prevalence of chronic subdural hematoma (CSDH), we investigated the relationship between sex differences and clinical features of CSDH. Methods We retrieved a large collection of clinical factors from CSDH patients between August 2011 and May 2019, and analyzed the differences and similarities in the clinical data and outcomes between men and women. Results In total 1,307 CSDH patients were enrolled in this study. When we did not account for age, a greater proportion of women relative to men manifested diabetes (p = 0.001) and cardiac disease (p = 0.035) prior to the onset of CSDH. Regarding recovery outcome and recurrence rate, we observed no significant differences between men and women. The sole difference between women and men after surgery was that women experienced more complications than men (p = 0.044), and both length of hospital stay (p < 0.001, B = 0.159, Exp [B] = 1.172, 95% CI = 1.078–1.274) and the presence of cardiac disease (p = 0.002, B = 2.063, Exp [B] = 7.867, 95% CI = 2.167–28.550) were identified as independent risk factors. After accounting for age, women with CSDH exhibited more frequent disorders of consciousness at admission than men in group of ≤ 40-year-old patients (p = 0.018), while proportion of women with diabetes was higher than that of men in 41–79 year-old group (p < 0.001). However, women after surgery experienced more complications (p = 0.047), longer length of hospital stays (p = 0.005), and higher mortality at discharge (p = 0.035) than men in middle-aged group. Finally, length of hospital stay (p < 0.001, B = 0.186, Exp [B] = 1.205, 95% CI = 1.091–1.331) and cardiac disease (p = 0.017, B = 2.040, Exp [B] = 7.693, 95% CI = 1.430–41.372) impacted occurrence of complications in women 41–79-year-old, while duration of drainage catheter use (p < 0.001, B = 1.132, beta = 0.280) and complications (p < 0.001, B = 5.615, beta = 0.366) were identified as independent risk factors for length of hospital stay in the same group of women. Conclusions Although sex differences did not constitute a crucial factor in all the CSDH patients, we still need to pay closer attention to disparities between men and women with respect to complications, length of hospital stay, and mortality at discharge in the various age groups (particularly with respect to 41–79 year-old women patients), to provide satisfactory management and treatment of CSDH patients.